Manajemen Komunikasi Instruksional Dosen dalam Meningkatkan Keterlibatan Mahasiswa - Cahyadi, Wahyu Choerul (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
This article examines lecturers’ instructional communication management in enhancing student engagement in the classroom. Student engagement is a crucial indicator of successful learning in higher education, as it is closely related to motivation, participation, and learning outcomes. This study aims to analyze the concept of lecturers’ instructional communication management and its role in fostering students’ cognitive, affective, and behavioral engagement. The research employs a literature review method by analyzing relevant books and scholarly journal articles related to communication theory, management, instructional communication, and student engagement. The findings indicate that effective instructional communication management includes clear planning of instructional messages, appropriate selection of communication strategies, dialogical management of classroom interactions, optimal utilization of learning media, and the provision of constructive feedback. Well-managed instructional communication has been shown to create a conducive and participatory classroom atmosphere, thereby enhancing student engagement in the learning process. In conclusion, lecturers’ instructional communication management plays a strategic role in improving the quality of learning in higher education and needs to be continuously developed as an integral part of lecturers’ professionalism.